The Types of Conversational Implicature in “Gifted” movie - Nurhidayah; Yassi Abdul Hakim; Sukmawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study is a pragmatic context of conversational implicature. It aimed to identify the types of conversational implicature and the non-observance maxim of cooperative principles expressed by the characters in a movie entitled Gifted. The objectives of the research are to identify the types of conversational implicature by the characters in the movie. This research applied a mixed method (descriptive qualitative method and quantitative method) to analyze the data. The data were in the form of utterances in the movie which were organized and analyzed based on Grice’s theory of conversational implicature. The findings of this research are explained as follows: particularized conversational implicature is found as the most dominant type of conversational implicature performed by the characters in the movie since most of the implied meanings needed background knowledge.